1967
DOI: 10.1099/00221287-49-1-115
|View full text |Cite
|
Sign up to set email alerts
|

The Toxic Effect of Oxygen Upon the Aerosol Survival of Escherichia coli B

Abstract: S U M M A R YAt high relative humidity (RH) similar survivals were obtained for storage in oxygen, air or nitrogen. At low RH the survival in nitrogen was much greater than that in air or in a 20 % (v/v) oxygen + 80 % (v/v) nitrogen mixture, in which the survivals were similar. In oxygen alone, survival was even lower than in air. Hence oxygen, or a trace contaminant in it, was responsible for the poorer survival in air than in nitrogen. The mechanism of death caused by oxygen is discussed. I N T R O D U C T I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
4
27
0
Order By: Relevance
“…This effect, and that caused by RH changes before collection, indicated, as for the other three strains of E. coli studied, that the manner in which water enters the bacterium during collection influences the survival. Oxygen toxicity was less apparent with E. coli K I~ HfrC than, for example, E. coli B (Cox, 1966a;Cox & Baldwin, 1967)~ probably owing to the poor survival of the former in nitrogen at low RH (in the absence of protective agents). The action of glycerol and raffinose was very similar to that with E. coli JEPP (Cox, 1967)~ and again showed that at low RH a protective agent (namely rafiose) outside the cell wall was able to confer stability.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This effect, and that caused by RH changes before collection, indicated, as for the other three strains of E. coli studied, that the manner in which water enters the bacterium during collection influences the survival. Oxygen toxicity was less apparent with E. coli K I~ HfrC than, for example, E. coli B (Cox, 1966a;Cox & Baldwin, 1967)~ probably owing to the poor survival of the former in nitrogen at low RH (in the absence of protective agents). The action of glycerol and raffinose was very similar to that with E. coli JEPP (Cox, 1967)~ and again showed that at low RH a protective agent (namely rafiose) outside the cell wall was able to confer stability.…”
Section: Discussionmentioning
confidence: 98%
“…162). Of the four coli strains studied, E. coli ~1 2 HfrC was the most unstable at high and at low RH, and was a good organism with which to study death mechanisms other than oxygen toxicity (Cox & Baldwin, 1967), because of the extent of viability loss when sprayed from distilled water into a nitrogen atmosphere. The minimum at 85% RH was very similar to that found at the same RH for E. coli B, but was very apparent at a much shorter aerosol age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial survival in aerosols depends on a number of factors including relative humidity, composition of the gaseous environment and the compositions of both spray and collecting fluids (Webb, 1960;Cox, 1966a, b ;Benbough, 1967;Cox & Baldwin, 1967). Comparatively little is known about the effect of aerosolization upon the integrity of bacterial walls and membranes.…”
Section: Introductionmentioning
confidence: 99%